Mapping H i 21-cm in the Klemola 31 group at z = 0.029: emission and absorption towards PKS 2020−370. Issue 2 (1st July 2022) - Maina, E K; Mohapatra, Abhisek; Józsa, G I G; Gupta, N; Combes, F; Deka, P; Wagenveld, J D; Srianand, R; Balashev, S A; Chen, Hsiao-Wen; Krogager, J-K; Momjian, E; et al.
ABSTRACT: We present MeerKAT Absorption Line Survey (MALS) observations of the H i gas in the Klemola 31 galaxy group ( z = 0.029), located along the line of sight to the radio-loud quasar PKS 2020−370 ( z = 1.048). Four galaxies of the group are detected in H i emission, and H i absorption is also detected in front of PKS 2020−370 in Klemola 31A. The emission and absorption are somewhat compensating on the line of sight of the quasar, and the derived column density of the absorption appears underestimated, with respect to the neighbouring emission. A symmetric tilted-ring model of Klemola 31A, assuming the absorbing gas in regular rotation in the plane, yields a rather high spin temperature of 530 K. An alternative interpretation is that the absorbing gas is extra-planar, which will also account for its non-circular motion. The Na i /Ca ii ratio also suggests that the absorbing gas is unrelated to cold H i disc. Two of the galaxies in the Klemola group are interacting with a small companion, and reveal typical tidal tails, and velocity perturbations. Only one of the galaxies, ESO 400−13, reveals a strong H i deficiency, and a characteristic ram-pressure stripping, with a total asymmetry in the distribution of its gas. Since a small galaxy group as Klemola 31 is not expected to host a dense intra-group gas, this galaxy must be crossing the group at a very high velocity, mostly in the sky plane.